Application of least mean square algorithm to suppression of maglev track-induced self-excited vibration - Zhou, D.F.; Li, J.; Hansen, C.H. (Journal of sound and vibration, 2011)
Track-induced self-excited vibration is commonly encountered in EMS (electromagnetic suspension) maglev systems, and a solution to this problem is important in enabling the commercial widespread implementation of maglev systems. Here, the coupled model of the steel track and the magnetic levitation system is developed, and its stability is investigated using the Nyquist criterion. The harmonic balance method is employed to investigate the stability and amplitude of the self-excited vibration, which provides an explanation of the phenomenon that track-induced self-excited vibration generally occurs at a specified amplitude and frequency. To eliminate the self-excited vibration, an improved LMS (Least Mean Square) cancellation algorithm with phase correction (C-LMS) is employed. The harmonic balance analysis shows that the C-LMS cancellation algorithm can completely suppress the self-excited vibration. To achieve adaptive cancellation, a frequency estimator similar to the tuner of a TV receiver is employed to provide the C-LMS algorithm with a roughly estimated reference frequency. Numerical simulation and experiments undertaken on the CMS-04 vehicle show that the proposed adaptive C-LMS algorithm can effectively eliminate the self-excited vibration over a wide frequency range, and that the robustness of the algorithm suggests excellent potential for application to EMS maglev systems. ► We construct the maglev electromagnet–track coupled model and examine its stability. ► We employ the harmonic balance method to investigate the amplitude of the vibration. ► An adaptive LMS algorithm with phase correction is employed to cancel the vibration. ► The analysis shows that the presented algorithm can totally eliminate the vibration. ► The presented algorithm is validated by numerical simulation and experiments.